Menu Engineering Approach to Determine Sales Strategy at Senja Eatery Labuan Bajo Restaurant - Putu Gita Suari Miranti; Made Satria Pramanda Putra; Layla Fickri Amalia; Ida Ayu Elistyawati (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to determine the right menu sales strategy in Senja Eatery Restaurant Labuan Bajo by evaluating the menu using the Menu Engineering approach based on its profitability and popularity level. The menu items analyzed are the Main Course menu with a total of 21 items. The research method used is quantitative descriptive with the source of result data. The results of this study are, menu items classified into 4 categories, 1 menu item is classified as Stars menus, 5 menu items are classified as Puzzles menu, 9 menu items are classified as Plow horses menus and the remaining 6 are classified as Dogs menus. The sales strategy applied to each menu category, namely the Stars menu, is to place it in a special place on the menu. For menu puzzles, lowering the selling price can increase sales while promoting it in all marketing media lines. The strategy for the Plow horses menu, maintain the menu items on the menu and make the menu more profitable by increasing the price. The strategy for the Dogs menu, eliminate the dogs menu items from the menu and replace them with other dishes that show potential profitability and popularity.